USING PORO ENGLISH APPLICATION TO IMPROVE STUDENTS’ PRONUNCIATION LEARNING ENGLISH AT UPT SPF SMPN 35 MAKASSAR - Wa Bonti Kilwakit; Hj.St. Haliah Batau; Muliati Muliati (Publikasi dan UKI Press UKI Toraja., 2023)
The research explores android-based learning media and applies the learning technique to counter this issue. This study investigates the poro English application in teanching English pronunciation in the classroom.It aims to identify student’s responses toward the application in learning English pronunciation in which students of ninth grade of SMP Negeri 35 Makassar. This study using a qualitative method to explore teaching and learning English pronunciation in the classroom using the poro english application. The data were collected in two main instruments: observation and interviews.The observation explored the process of applies the poro English application in teaching English pronunciation. While the interviews were administered to reveal the student’s response. The result showed that poro English application in teaching English pronunciation could be applied in the classroom. In particular, most students responded positively to using the application in the learning activities. For example,they said that application really helped them to learn and made it easier for them to practice pronunciation.